Odor exploration behavior of the domestic pig (Sus scrofa) as indicator of enriching properties of odors - Rørvang, Maria Vilain; Schild, Sarah-Lina Aagaard; Stenfelt, Johanna; Grut, Rebecca; Gadri, Moses A.; Valros, Anna; Nielsen, Birte L.; Wallenbeck, Anna (Frontiers in Behavioral Neuroscience, 2023)
Although the sense of smell in pigs is widely recognized as being highly developed, surprisingly little is known about their sensory ability. This study aimed to a) identify which non-social odors pigs were able to detect and distinguish between, b) investigate the types of behavior expressed when exploring odors and, c) compare pigs’ responses to the different odors to evaluate their interest in the odors. Growing pigs (N=192) of crossbred commercial breeds were enrolled in the experiment (32-110 days of age, weighing 64.9±10.1kg). Littermate pairs of opposite sex were tested in test pens with two odor insertion points in the pen wall, 55 cm apart. All pigs were habituated to the test pens and experimenters. Twelve odors were tested (8 essential oils and 4 synthetic perfumes) in groups of three odors, with each pig pair tested once with one set of three odors (all possible orders of the three odors were tested on 24 pairs in total), always against a non-odor control (demineralized water). In a test, each of the three odors were presented during 3 trials in a row (a total of 9 trials per test; trial duration: 1 min; inter-trial breaks: 2 min; total test duration: 25 min). Response variables included: duration of sniffing, feeding-related behavior (licking, biting and rooting), agonistic behavior (biting, displacement and pushing) and no approach of the odor or control, recorded throughout each 1-min odor presentation. All pigs sniffed an odor less when repeatedly presented (LMM: all odors P<0.05), and significantly longer at the subsequent presentation of a new odor (LMM (3rd vs. 1st presentations): P<0.001). Specific odor and odor type (essential oil vs. synthetic perfume) had no significant effect on sniffing duration. Overall, feeding-related behavior and agonistic behavior were expressed significantly more when pigs explored the odor compared with the control insertion point (Paired t-tests: P<0.001), and specific odor only affected the expression of feeding-related behavior. Collectively, pigs express sniffing, agonistic, and feeding-related behavior when exploring odors, which suggests that pigs perceive odors of non-social origin as a resource. Odors may thus constitute relevant enrichment material for pigs.